2005
DOI: 10.1556/avet.53.2005.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Detection of respiratory and enteric shedding of bovine coronaviruses in cattle in Northwestern Turkey

Abstract: Bovine coronavirus (BCoV) is an important cause of diarrhoea in calves, winter dysentery in adult cattle and respiratory tract disease in feedlot cattle. Serum, faecal and nasal swab samples were collected from a total of 96 cattle with clinical signs in 29 barns of 23 villages in Northwestern Turkey. The cattle were subdivided into 3 distinct age groups (0-30 days old, 4-12 months old and 2-7 years old). An indirect antigen-capture ELISA and an antibody-detection ELISA as well as geometric mean BCoV antibody … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
28
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 23 publications
4
28
0
4
Order By: Relevance
“…Similar results were found in one case–control study involving 380 calves . However, studies including small numbers of calves (n < 100) identified numerical but not statistical association between BCoV in fecal or nasal samples and clinical signs . Discrepancies between studies can be explained, at least in part, by differences in the source population, methodology, especially, the samples size used in the different investigations …”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Similar results were found in one case–control study involving 380 calves . However, studies including small numbers of calves (n < 100) identified numerical but not statistical association between BCoV in fecal or nasal samples and clinical signs . Discrepancies between studies can be explained, at least in part, by differences in the source population, methodology, especially, the samples size used in the different investigations …”
Section: Discussionsupporting
confidence: 71%
“…BCoV is the causative agent of diarrhea in newborn calves, winter dysentery in adult cows, and respiratory tract illness in calves and adults . However, some studies have identified numerical but not statistical association between BCoV in fecal or nasal samples and clinical signs . Cases of BCoV enteritis occur in both dairy and beef herds, with clinical signs developing between 5 and 30 days of life and a peak of incidence between days 7 and 10 .…”
mentioning
confidence: 99%
“…Other possible explanations for this result could be the lower sensitivity of ELISA compared with RT-PCR assay (Cho et al, 2001a). However, in a survey conducted in Turkey during 2001-2002 using the same indirect antigen-capture ELISA, the BCoV detection rate was 28.1% (Hasoksuz et al, 2005), suggesting that BCoV-associated diarrhea in Argentinean calves may be lower than in other countries.…”
Section: Discussionmentioning
confidence: 93%
“…The BCoV respiratory disease has been described in different areas worldwide, including the United States, 14,19,23 Canada, 8 Turkey, 13 Japan, 17 Finland, 1 and Sweden. 11 In the Finland study, 1 various microorganisms were detected in association with BCoV, including mycoplasmas (mainly Mycoplasma bovis and Mycoplasma dispar), Pasteurella multocida, Mannheimia haemolytica, and Arcanobacterium pyogenes, as well as other viral pathogens, specifically, BPIV3, BRSV, and bovine adenoviruses.…”
Section: Discussionmentioning
confidence: 99%